Improving Implementation Methods Subjects Study Group At Ips At Class Vi Sdn 03 Padang District Of Lengayang Marapalam Academic Year 2015/2016 - Lisdaini Lisdaini (Fakultas Sastra Universitas Ekasakti, 2017)
Function lessons Social Science (IPS) Elementary School is to develop a rational attitude about social phenomena as well as an insight into the development of Indonesian society and mas world in the past and the present. While the purpose of social studies in primary school is to take the knowledge and basic skills that are useful for students in daily life and be able to develop an understanding of the development of Indonesian society since the past until the present. In the evaluation, the teaching of social studies for students of SD Negeri 03 Padang District of Lengayang Marapalam Academic Year 2015/2016 industrious and keen to learn, they will be easier to work on and solve the problems it faces, and they will be fond of social studies for social studies is not an exact lesson or an exact science that requires a definite answer. This study is an action research (PTK) using the model Kemmis and MC. Taggart (1988). Kemmis develop a model which would exist sarkan spiral of self-reflection system starts with a plan, action, observation and reflection, for re-planning is the basis for a square - square troubleshooting. Student achievement SD Negeri 03 Padang District of Lengayang Marapalam Academic Year 2015/2016 class VI is still not satisfactory. This research is a class action ( classroom action research ). In the initial condition (prasiklus) achievement of sixth grade social studies on the competence of the formation of market prices are still low. Of the 22 students who score less than KKM 14 students (53.57%), within the limits of KKM there are five students (25%) and exceeded the limits of existing KKM 3 students (21, 43%) with an average grade 66.75.